Pesquisas sobre nematóides da família Mononchidae encontrados no Brasil - Lordello, Luiz Gonzaga E. (Anais da Escola Superior de Agricultura Luiz de Queiroz, 1970)
The following items concerning Mononchid nematodes are dealt with in this paper: a) A historical review of the family Mononchidae from the establishment of the type genus Mononchus Bastian, 1865, to our present days. Sixteen genera are recognized in the family. Morphology, based particularly on species found in Brazil. c) A review of the role assumed by the Mononchidae as members of the biotic complex of soil, with observations on behavior of species found in Brazil. Two Mononchus papillatus females showed in the gut larvae apparently belonging to its own species, thus confirming occurrence of cannibalism. d) A description of a new species (Sporonchulus paucidentatus n. sp.) and redescriptions of a few other forms that the author found in the Country for the first time. These were: Sporonchulus dentatus, Mononchus papillatus, Mylonchulus incurvus and Mylonohulus sigmaturus. A species closely resembling M. incurvus is described and provisionaly named Mylonchulus sp. Diagnosis of S. paucidentatus n. sp. - A Sporonchulus having the dimensions cited in the description, an arcuated tail, and stoma armed with 4 subventral denticles only. e) A key for separating the genera known to occur in Brazil. f) A list of the species of Mononchidae found in Brazil, with citation of the pertinent literature and observations on distribution, morphology, habits, etc. g) Keys for separating the species of the genera found in the Country.